Analisis Proses Pembelajaran di Masa Pandemi Covid-19 Terhadap Kebiasaan Belajar Siswa di SMA Negeri 8 Palu - Purnamasari, Reski; 'Nisa, Zumrotin (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This study aims to determine changes in student learning patterns and teacher efforts in dealing with changes in student learning patterns at SMAN 8 Palu during the covid-19 pandemic. The method used is descriptive qualitative, with research subjects 2 teachers of geography and 4 students. Data collection techniques by observation, interviews and documentation. The research instrument used an interview guide. The data analysis used is interactive model data analysis. The results showed that; 1) changes in student learning patterns related to making schedules and their implementation in learning, reading and taking notes, repeating geography lesson materials, concentrating on geography learning and doing assignments in geography learning. Changes in student learning patterns have not been well and optimally; 2) the teacher's efforts in changing student learning patterns during the covid-19 pandemic, namely changes in student learning patterns can be carried out but are still not optimal, due to several factors and obstacles that are owned by the students themselves.